2009
DOI: 10.5539/ijbm.v3n12p177
|View full text |Cite
|
Sign up to set email alerts
|

Causal Links between Foreign Direct Investment and Exports: Evidence from Malaysia

Abstract: Malaysia has encouraged foreign investment not only for its role in technology transfer but also for its contribution to Malaysian exports. Therefore, the aim of this study is to investigate empirically the causal relationship between FDI inflows and exports in Malaysia. The methodologies of stationarity of time series and the multivariate Granger concept of causality were employed to carry out the investigation. The finding that time series variables are cointegrated implies that there is a long term relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…See (table 2). Inflation is negatively and insignificantly related with growth and one percent decrease in inflation and GDP rise in 0.03 percent as also originate by Samsu et al (2009). The result show that inflation is not higher rate of SAARC countries and insignificant at 5 percent level.…”
Section: Hausman Testmentioning
confidence: 71%
“…See (table 2). Inflation is negatively and insignificantly related with growth and one percent decrease in inflation and GDP rise in 0.03 percent as also originate by Samsu et al (2009). The result show that inflation is not higher rate of SAARC countries and insignificant at 5 percent level.…”
Section: Hausman Testmentioning
confidence: 71%
“…The empirical research by Samsu et al (2008) using the vector error correction model can not find causality in the short run between FDI inflows and exports, but validates the long-run positive effect from investment inflows to exports. Similar studies also indicate that if the investor and recipient economies of FDI vary widely regarding resource endowments, then the host country export can be expanded (Liu et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
“…To make the effective use of FDI, host economies should identify its comparative advantage and very importantly FDI should supplement but not substitute for capital resources (Samsu et al,2008).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to those authors Jayachandran and Seilan (2010) and Alıcı and Ucal (2003) who have argued that there is no relationship between foreign direct investment and exports, others Prasanna (2010); Gunawardana and Sharma (2009); Liu and Chang (2003); Zhang (2005); Vukšić (2005) and Vural and Zortuk (2011) insist on the existence of a strong positive effect of FDI on export performance. Given the importance accorded to foreign direct investment and exports in economic growth, the relationship between both variables emerges as a significant topic of research (Samsu et al, 2008). The relationship between both variables has been subject to various classifications within the literature, and the following is a detailed account of these classifications.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…Although they differ with regard to the periods covered as well as the economies analysed, the studies by Dritsaki et al (2004); Samsu et al (2008); Liu et al (2001); Johnson (2006) and Ahmed et al (2007) have strongly suggested that there is a unidirectional causal relationship from FDI to export, while Temiz and Gökmen (2009) found that the unidirectional causal relationship is from export to FDI. Thestudy by Liu et al (2002) revealed a bidirectional causal relationship between FDI and exports.…”
Section: Empirical Studiesmentioning
confidence: 99%